Physical mapping of human chromosomes by repetitive sequence fingerprinting. - Stallings, R L (1990)
We have developed an approach for identifying overlapping cosmid clones by exploiting the high density of repetitive sequences in complex genomes. Individual clones are fingerprinted, using a combination of restriction enzyme digestions followed by hybridization with selected classes of repetitive sequences. This "repeat fingerprinting" technique allows small regions of clone overlap (10-20%) to be unambiguously assigned. We demonstrate the utility of this approach, using the fingerprinting of 3145 cosmid clones (1.25 x coverage), containing one or more (GT)n repeats, from human chromosome 16. A statistical analysis was used to link these clones into 460 contiguous sequences (contigs), averaging 106 kilobases (kb) in length and representing approximately 54% (48.7 Mb) of the euchromatic arms of this chromosome. These values are consistent with theoretical calculations and indicate that 150- to 200-kb contigs can be generated with 1.5 x coverage. This strategy requires the fingerprinting of approximately one-fourth as many cosmids as random strategies requiring 50% minimum overlap for overlap detection. By "nucleating" at specific regions in the human genome, and exploiting the high density of interspersed sequences, this approach allows (i) the rapid generation of large (greater than 100-kb) contigs in the early stages of contig mapping and (ii) the production of a contig map with useful landmarks for rapid integration of the genetic and physical maps.